2001
DOI: 10.1046/j.1432-1033.2001.02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression of N-terminal truncated mutants of the membrane bound mouse, rat and human flavoenzyme dihydroorotate dehydrogenase A versatile tool to rate inhibitor effects?

Abstract: Mammalian dihydroorotate dehydrogenase, the fourth enzyme of pyrimidine de novo synthesis is an integral protein of the inner mitochondrial membrane that faces the intermembrane space and is functionally connected to the respiratory chain via ubiquinone. Here, we describe the first cloning and analyzing of the complete cDNA of mouse dihydroorotate dehydrogenase. Based on our recent functional expression of the full-length rat and human dihydroorotate dehydrogenase, here we expressed N-terminal-truncated C-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 14 publications
5
43
1
1
Order By: Relevance
“…The availability of several additional fungal genome sequences, in particular those of basidiomycetous origin, will surely clarify this issue. Interestingly, the heterolo- Our biochemical analysis of U. maydis DHODH revealed that the activity of the recombinant enzyme is significantly lower than that of mammalian DHODH (6 U/mg compared to 99 U/mg for the human enzyme) (55). The K m value of U. maydis DHODH is significantly higher (43 M for DHO) than that of human DHODH (9.7 M for DHO) (55).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The availability of several additional fungal genome sequences, in particular those of basidiomycetous origin, will surely clarify this issue. Interestingly, the heterolo- Our biochemical analysis of U. maydis DHODH revealed that the activity of the recombinant enzyme is significantly lower than that of mammalian DHODH (6 U/mg compared to 99 U/mg for the human enzyme) (55). The K m value of U. maydis DHODH is significantly higher (43 M for DHO) than that of human DHODH (9.7 M for DHO) (55).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the heterolo- Our biochemical analysis of U. maydis DHODH revealed that the activity of the recombinant enzyme is significantly lower than that of mammalian DHODH (6 U/mg compared to 99 U/mg for the human enzyme) (55). The K m value of U. maydis DHODH is significantly higher (43 M for DHO) than that of human DHODH (9.7 M for DHO) (55). In both cases, these values were determined for recombinant proteins lacking their N-terminal transmembrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…4B, NITD-982 inhibited DHODH activity with a 50% inhibitory concentration (IC 50 ) of 103 nM. As a positive control, brequinar, a known DHODH inhibitor (46), exhibited an IC 50 of 2.1 nM.…”
Section: Identification Of Nitd-982mentioning
confidence: 99%
“…В ходе этих исследований были зафиксиро-ваны эмбриотоксические и тератогенные эффекты териф-луномида у крыс и кроликов. Стоит, однако, отметить, что терифлуномид ингибирует фермент ДГОДГ у крыс силь-нее, чем ДГОДГ человека [29], в результате чего его анти-пролиферативная активность у крыс в 145 раз больше [21]. Это может объяснить, почему схожая плазменная концентрация терифлуномида приводит к тератогенному эффекту у крыс, но не у человека.…”
Section: терифлуномид оказывая иммуномодулирующий эффект снижает срunclassified